Analysis of the intervention of psychological support groups to professionals of a health institution in coping with the covid-19 pandemic (Research, Society and Development, 2022)
Health institutions, especially hospitals, became the center of combat during the covid-19 pandemic. Consequently, health professionals have had to deal with changes and new demands inside and outside of work, which can impact on their mental health. In a large hospital in the city of São Paulo, an intervention was carried out by psychological support groups for the institution's employees, aiming at the care, promotion and prevention of mental health in the face of the covid-19 pandemic. Therefore, this study proposed to analyze the data from these interventions by support groups for health professionals who acted in the face of the covid-19 pandemic, from March to July 2020, and the relationship between the reports presented and the health care unit. work, in addition to considering the moment in which the groups were held. It is also expected to carry out a content analysis on the reports presented, defining the main thematic axes addressed. For this, data from the worksheet for monitoring the action of the Psychology Unit of the hospital were used, and an analysis were carried out using descriptive statistics and content analysis.